Penggunaan Bahasa Indonesia yang benar sebagai representasi kesantunan mahasiswa - Dewi Ayu Anggraeni; Ananda Dwitha Yuniar (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2021)
In an educational environment, Lecturers apply the correct way of speaking in Indonesian to students as a sign of maintaining social and cultural values. Students are the younger generation who play an important role for the nation, so students are trained to be polite according to ethics, especially in language. So that students are expected to use the correct Indonesian language in communicating. The correct Indonesian language is used as a unifying language for the nation besides that it also functions as a form of language politeness for students. Therefore, this paper describes the representation of politeness of the State University of Malang Sociology students in using the correct Indonesian language. The research method used is qualitative and data collection techniques by interview. The results obtained are that for students using the correct Indonesian language is something important because lecturers are parents at campus, have high knowledge, have a lot of experience than students, and are older than students. To realize politeness towards lecturers, when students communicate with lecturers it is very necessary to use correct Indonesian so that students have a good image in front of the lecturer, so that the lecturer will label students as polite to lecturers. Dalam lingkungan pendidikan, Dosen menerapkan cara bertutur kata dengan menggunakan bahasa Indonesia yang benar kepada mahasiswa sebagai tanda untuk menjaga nilai sosial dan budaya. Mahasiswa adalah generasi muda yang berperan penting bagi bangsa, sehingga mahasiswa dilatih untuk bersikap santun sesuai etika terutama dalam berbahasa. Sehingga mahasiswa diharapkan menggunakan Bahasa Indonesia yang benar dalam berkomunikasi. Bahasa Indonesia yang benar digunakan sebagai bahasa pemersatu bangsa, selain itu juga berfungsi sebagai wujud kesantunan berbahasa bagi Mahasiswa. Oleh karena itu, tulisan ini menjelaskan representasi kesantunan mahasiswa Sosiologi Universitas Negeri Malang dalam menggunakan bahasa Indonesia yang benar. Metode penelitian yang digunakan adalah kualitatif dan teknik pengumpulan data dengan wawancara. Hasil yang diperoleh yaitu bagi mahasiswa menggunakan Bahasa Indonesia yang benar adalah sesuatu yang penting karena dosen adalah orangtua di kampus, memiliki ilmu pengetahuan yang tinggi, memiliki banyak pengalaman daripada mahasiswa, serta lebih tua daripada mahasiswa. Untuk mewujudkan kesantunan terhadap dosen, ketika mahasiswa berkomunikasi dengan dosen sangat diperlukan menggunakan bahasa Indonesia yang benar agar mahasiswa memiliki citra yang baik didepan dosen, sehingga dosen akan memberi labelling sebagai mahasiswa yang santun terhadap dosen.